Short- and long-term participation tax rates and their impact on labor supply - Charlotte Bartels; Nico Pestel (International Tax and Public Finance, 2016)
Generous income support programs as provided by European welfare states have often been blamed to hamper employment. This paper investigates the importance of incentives inherent in the tax-benefit system for the individual decision to take up work. Using German microdata over the period 1993-2010, we find that recent reforms in Germany increased work incentives at the extensive margin measured by the participation tax rate (PTR), particularly for low-income individuals. Work incentives are even higher if the time horizon is extended to more than one year, pointing at an overestimation of the disincentives by standard measures. Regression analysis reveals that a decrease in the PTR increases the probability of taking up work significantly.
Additional information: The final publication is available at Springer via http://dx.doi.org/10.1007/s10797-016-9400-9
Keywords: H24; H31; J22; J65; 330; Labor force participation; Work incentives; Welfare; Unemployment insurance; Income taxation